UNVEILING SELF: IDENTITY IN AMY TAN’S THE CHINESE SIAMESE CAT - P., Vasanthi; R., Ajith (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Amy Tan’s The Chinese Siamese Cat examines the exploration of identity. Through the narrative of a Siamese cat explaining the changing colour of her kittens’fur as they age, Tan delves into themes of self-recognition and cultural identity. The story, set against the backdrop of a classic Chinese folktale, serves as an allegory for broader socio-cultural dynamics. This analysis highlights how Tan uses the Siamese cat’s journey to reflect on issues of ethnic, gender, and cultural identity, aligning with Marxist perspectives on class struggle and social categorization. The examination reveals how the quest for personal identity intertwines with societal structures, offering insights into the challenges of self-definition amidst varying social expectations and power dynamics.